Interprofessional collegiality and workplace abuse among healthcare workers in eastern Uganda: A convergent mixed-methods study - Tweheyo Ronald; Eric Oradi; Kennedy Pangholi; Olga Olaki Ariga; Barnabas Walozi; Kelvin Muwanguzi; Flavia Nakyejwe; Rhoda Mwesigwa; Joshua Epuitai (PLoS ONE, 2026)
Interprofessional collegiality reflects mutual respect, empathy and solidarity among different health professionals. Limited studies have explored interprofessional collegiality in Uganda. This study was conducted to determine the magnitude of interprofessional collegiality among healthcare workers in Eastern Uganda. We used a mixed-methods study design. The study was conducted among healthcare workers in two institutions in Eastern Uganda. We used the Practice Environment Scale to assess interprofessional collegiality among a sample size of 136 healthcare workers. The Likert Scale was used to assess the different dimensions of interprofessional collegiality. Ethical approval was obtained. Descriptive statistics were used for quantitative data, while thematic analysis was used for qualitative data. The majority of the participants were nurses/midwives (48%), allied health professionals (40%) and medical doctors (11%). The majority (65%) of participants strongly agreed and agreed that there was effective interprofessional collaboration in their workplace. Participants strongly agreed/agreed that there were good working relations (60%) and good teamwork (56%) between nurses/midwives and medical doctors. However, uncivil behaviours were common among healthcare workers, including psychological/emotional abuse (78%), physical abuse (4%), and sexual abuse (4%). In a qualitative study, uncivil behaviours occurred in the form of cold wars, name-calling, political interference, silent hatred, psychological stress, demotivation, absenteeism, and poor work relations. Poor collegial relations occurred from the individual (gender bias, perceived lack of capacity, poor supervision and leadership), interpersonal (lack of interpersonal respect, perceived lack of role clarity) and institutional factors (workload, poor working conditions, and maldistribution of incentives). Despite the high interprofessional collegiality reported between nurses/midwives and medical doctors, workplace abuse among healthcare workers was high in our setting. Policymakers could prioritise strategies that address individual, interpersonal and institutional factors that result in poor work relations among healthcare workers.